COVID-19 and food export restrictions: Comparing today’s situation to the 2007/08 price spikes - Hepburn, Jonathan; Laborde Debucquet, David; Parent, Marie; Smaller, Carin (International Institute for Sustainable Development, 2020)
This policy brief draws on the International Food Policy Research Institute’s (IFPRI’s) COVID-19 Food Trade Policy Tracker to compare how governments have reacted to the current crisis with how they did during the 2007/08 food price spike.